2023
DOI: 10.1007/s40292-023-00574-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Incident New-Onset Arterial Hypertension After COVID-19 Recovery: A Systematic Review and Meta-analysis

Abstract: Introduction Arterial Hypertension (HT) has been described as a common comorbidity and independent risk factor of short-term outcome in COVID-19 patients. However, data regarding the risk of new-onset HT during the post-acute phase of COVID-19 are scant. Aim We assess the risk of new-onset HT in COVID-19 survivors within one year from the index infection by a systematic review and meta-analysis of the available data. Methods Data were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…They proposed some possible explanations for the abnormalities mentioned above: (1) activation of the RAAS or the sympathetic nervous system, (2) endothelial dysfunction, (3) delayed resolution of inflammation, or (4) hypoxia and ischemia. A meta-analysis of over 19 million people reported that post-COVID-19 individuals had an additional 70% risk of developing new-onset hypertension within 7 months of acute infection [ 40 ]. Although we could not diagnose hypertension in our post-COVID population, they tended to have higher SBP, DBP, and MBP in all exercise steps, which may be due to this cohort being relatively young (average age under 40 years) and having suffered a mild infection that did not require hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…They proposed some possible explanations for the abnormalities mentioned above: (1) activation of the RAAS or the sympathetic nervous system, (2) endothelial dysfunction, (3) delayed resolution of inflammation, or (4) hypoxia and ischemia. A meta-analysis of over 19 million people reported that post-COVID-19 individuals had an additional 70% risk of developing new-onset hypertension within 7 months of acute infection [ 40 ]. Although we could not diagnose hypertension in our post-COVID population, they tended to have higher SBP, DBP, and MBP in all exercise steps, which may be due to this cohort being relatively young (average age under 40 years) and having suffered a mild infection that did not require hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…While our systematic review aimed to broaden the discussion on the influence of SARS-CoV-2 on blood pressure elevation, it is noteworthy that, despite discovering three studies contradicting the impact of COVID-19 on blood pressure, the majority of the analyzed studies align with the conclusions presented by Zuin et al [109]. Given the limited availability of studies specifically delineating arterial hypertension as a complication of COVID-19 infection, we opted to include all studies demonstrating blood pressure elevation as a consequence of COVID-19 infection.…”
Section: Limitationsmentioning
confidence: 53%
“…Recognizing the inherent limitations of this systematic review is crucial. Throughout our investigation, we identified only one meta-analysis by Zuin et al [109] that addressed the risk of developing hypertension in individuals with COVID-19. They proposed that newly diagnosed hypertension could be a noteworthy complication of severe COVID-19 infection, citing five supporting studies within their review.…”
Section: Limitationsmentioning
confidence: 99%
“…decreased physical activity, poor glycemic control and adherence to therapy) may have had an impact on aMR in the population without COVID-19 [ 21 ]. Moreover, some studies pointed to newly diagnosed HTN and DM after acute COVID-19 diagnosis, especially in severe cases [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%